Analisis Pengaruh Beban Kerja dan Disiplin Kerja terhadap Kinerja Karyawan di PT Jasa Prima Logistik BULOG Cabang DKI Jakarta dan Banten - Alya Nurjihan, Nadya; Kuwara Sari, Rycha; Puspitorini, Ferawaty (Yayasan Inovasi Akademi Nusantara, 2025)
This study aims to analyze the effect of workload and work discipline on employee performance at PT Jasa Prima Logistik BULOG, DKI Jakarta & Banten Branch. The research employs a quantitative approach using a survey technique, where data were collected through questionnaires distributed to 45 respondents. The analysis technique used is multiple linear regression with the assistance of IBM SPSS version 26 software.he results show that workload has a negative and insignificant effect on employee performance, with a t-value of -1.215 and a significance level of 0.231 (p > 0.05). This indicates that an increase in workload does not necessarily enhance employee performance and may even reduce productivity if the workload is excessive. Conversely, work discipline has a positive and significant effect on employee performance, with a t-value of 5.127 and a significance level of 0.000 (p < 0.05). This suggests that employees with a high level of discipline tend to be more productive, responsible, and effective in completing their tasks.Simultaneously, the F-test results indicate that workload and work discipline together have a significant impact on employee performance, with an F-value of 14.823 and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) test results show that 41.2% of the variation in employee performance can be explained by workload and work discipline variables, while the remaining 58.8% is influenced by other factors not examined in this study.The conclusion of this study is that work discipline is the primary factor contributing to improved employee performance, whereas excessive workload without proper management can negatively impact productivity. Therefore, PT Jasa Prima Logistik BULOG is advised to enhance employee discipline through more effective policies and manage workload proportionally to prevent adverse effects on employee well-being and productivity.